Transient Non-Inflammatory Vascular Sheathing in Combined CRVO and Cilioretinal Artery - Akram, Imran (Pakistan Journal of Ophthalmology, 2018)
To describe a case of evanescent sheathing of retinal vessels in a case of combined occlusion of the central retinal vein and Cilioretinal artery. The sheathing was non-inflammatory and resolved spontaneously after a few days. This was accompanied by significant visual improvement. No active treatment was offered to this patient. Even though transient vessel sheathing has been previously reported in retinal vein occlusion this is the first published report of transient vessel sheathing in association with combined central retinal vein and Cilioretinal artery occlusion. Key words: Transient sheathing, Central retinal vein occlusion, Cilioretinal artery.